Nutrient requirement and potassium nutrition in Persian cucumber with pruning to a single stem - Alejo-Santiago, Gelacio; Becerra-Venegas, Sergio Guadalupe; Bugarín-Montoya, Rubén; Aburto-González, Circe Aidín; Quiñones-Aguilar, Evangelina Esmeralda; Rincón-Enríquez, Gabriel; Juárez-Rosete, Cecilia Rocío (REVISTA TERRA LATINOAMERICANA, 2021)
In fertigation systems, proper management of potassium nutrition in Persian cucumber crop increases fruit quality. Similarly, nutrient extraction indexes are needed to establish mineral nutrition programs during the crop cycle. The aim of this research was to evaluate the effect of potassium nutrition and quantify the nutritional extraction in two varieties of Persian cucumber (Reehan and Khassib). The experimental design was factorial 2 × 4, the first factor was the two varieties of cucumber and the second factor the concentration of K+ in the nutrient solution, with concentrations of 5, 7, 9 and 11 meq L-1. The variables were: Cumulative fruit production (PAF), fruit number (NF), individual fruit weight (PIF), fruit diameter and total soluble solids (TSS). The analysis of variance indicated that there was an effect of factor interaction in PAF and NF (P ≤ 0.05). In both varieties, there were significant differences in all the quantified response variables, where Khassib showed the highest values (Tukey, P ≤ 0.05). For the nutritive solution factor, there were only significant differences in PAF and PIF. The highest PAF (Tukey, P ≤ 0.05) was obtained with nutrient solutions containing 9 and 11 meq K L-1; while the highest PIF occurred with 5, 7 and 9 meq K L-1. The potassium concentration in the nutrient solution showed a positive correlation with the content of total soluble solids in fruits of the Reehan variety (r = 0.999), but not in the Khassib variety (r = -0.6829). The nutritional requirement (kg) per ton of fresh fruit in Reehan was N 3.93, P 0.46, K 3.11, Ca 0.79 and Mg 1.30; while in Khassib N 5.87, P 0.49, K 3.11, Ca 0.85 and Mg 1.54.